Two new and rare psyllids (Hemiptera, Psylloidea) from French Polynesia - Percy, Diana M. (Zootaxa, 2025)
Two new psyllid species, Ctenarytaina elinae sp. nov. and Anomocephala rosiegeorgeorum sp. nov., are described from French Polynesia. Both are single island endemics known only from a small number of specimens. Ctenarytaina elinae sp. nov. is in the primarily Austro-Pacific genus Ctenarytaina Ferris & Klyver (Aphalaridae), and with the addition of C. elinae there are now three Ctenarytaina species in French Polynesia. Ctenarytaina elinae sp. nov. is endemic to Tahiti in the Society Islands, and although the host is unrecorded there is some evidence to suggest it may be Metrosideros (Myrtaceae). Previously monotypic, Anomocephala Tuthill (Triozidae), with the addition of A. rosiegeorgeorum sp. nov., now includes two species, and both of these are endemic to Rapa island in the southern Austral archipelago. Both the genus, Anomocephala, and the type species, Anomocephala unica Tuthill, 1942, are redescribed. The host plant of Anomocephala rosiegeorgeorum sp. nov. is likely Metrosideros collina. The new species names recognize entomologists working in the Pacific, and this contribution to this special issue honours one of the most prolific psyllid researchers and taxonomists, Daniel Burckhardt.